Fatty Liver Hemorrhagic Syndrome in the Backyard Chicken: A Retrospective Histopathologic Case Series. (July 2014) - Trott, K. A.; Giannitti, F.; Rimoldi, G.; Hill, A.; Woods, L.; Barr, B.; Anderson, M.; Mete, A.
Fatty liver hemorrhagic syndrome, characterized by sudden death in overconditioned hens due to hepatic rupture and hemorrhage, is one of the leading noninfectious idiopathic causes of mortality in backyard chickens. Nutritional, genetic, environmental, and hormonal factors, or combinations of these, have been proposed yet not proven as the underlying cause. In an attempt to characterize the hepatic changes leading to the syndrome, this retrospective case study examined 76 backyard chickens that were diagnosed with fatty liver hemorrhagic syndrome between January 2007 and September 2012 and presented for necropsy to the diagnostic laboratory of the California Animal Health and Food Safety Laboratory System. A majority of the birds were female (99%), obese (97.5%), and in active lay (69.7%). Livers were examined histologically, and the degree of hepatocellular vacuolation (lipidosis), the reticular stromal architecture, the presence of collagenous connective tissue, and vascular wall changes were evaluated and graded using hematoxylin and eosin, Gomori's reticulin, oil red O, Masson's trichrome, and Verhoeff-Van Gieson stains. Interestingly, there was no correlation between lipidosis and reticulin grades; hepatocellular lipidosis was absent in 22% of the cases and mild in 26% of the cases. Additionally, there was evidence of repeated bouts of intraparenchymal hemorrhage before the acute "bleed-out" in 35.5% of the cases. These data are not supportive of the previously proposed causes and provide a framework for future studies to elucidate the pathogenesis of this condition. Furthermore, the data shown in this study support hemorrhagic liver syndrome as a more accurate name, as hepatic lipidosis is absent in a significant proportion of ruptured livers.